1970
DOI: 10.3329/bjpt.v17i1.5393
|View full text |Cite
|
Sign up to set email alerts
|

Flowering and fruiting characteristics and biochemical composition of an endangered palm species (<i>Corypha taliera</i> Roxb.)

Abstract: Monitoring on the panicle initiation, flowering, fruiting and seedling characteristics of Corypha taliera has been carried out. Biochemical composition of fresh and dry flowers together with the pericarp of the fruits have been analysed. Fresh flowers, fruits, seeds, and pericarp and testa weighed 13.75 mg/flower, 19.46 g/fruit, 6.47 g/seed, 12.89 g/pericarp and testa, respectively. The length of fruits and seeds were c 3.34 cm and        c 2.33 cm, respectively while the breadth of the same were 3.14 cm and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 2 publications
(1 reference statement)
0
6
0
Order By: Relevance
“…The fruits of C. taliera were collected from the lone individual existed in the campus of the University of Dhaka and a voucher specimen was deposited at the department of Botany, University of Dhaka (Khondker et al 2010). The pericarp were separated from the seeds of dried fruits and made into powder.…”
Section: Collection Of Plant Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fruits of C. taliera were collected from the lone individual existed in the campus of the University of Dhaka and a voucher specimen was deposited at the department of Botany, University of Dhaka (Khondker et al 2010). The pericarp were separated from the seeds of dried fruits and made into powder.…”
Section: Collection Of Plant Materialsmentioning
confidence: 99%
“…Corypha taliera Roxb. locally known as Talipalm in Bangladesh, is a globally endangered species (Khondker et al 2010 belongs to the family Arecaceae. William Roxburgh discovered the plant in 1819 and reported it to be endemic to Bengal (Roxburgh 1820(Roxburgh , 1832Basu 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Significant evidence regarding economic value, botanical information including panicle initiation, flowering and fruiting as well as biochemical composition of flowers and fruits of the plant have been recorded primarily (Shoeb et al, 2015;Khondker et al 2010). Recently, phytochemical screening revealed that the unripe fruits contain significant bioactive molecules including βsitosterol, β-amyrin, betulinic acid, lupeol (Chowdhury et al, 2013), palmitic, myristic, linoleic, arachidic, stearic, lignoceric acids (Shoeb et al, 2013 and (Shoeb et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…There are four species of the genus Corypha, namely Corypha taliera, C. umbraculifera, C. elata and C. macropoda available in the Indian subcontinent. C. taliera locally known as Talipalm, is a globally endangered species (Khondker et al 2010). The existence of C. taliera in Bangladesh was identified by late Prof. Salar Khan in 1950 in the Dhaka University Campus, Dhaka (Khondker et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…C. taliera locally known as Talipalm, is a globally endangered species (Khondker et al 2010). The existence of C. taliera in Bangladesh was identified by late Prof. Salar Khan in 1950 in the Dhaka University Campus, Dhaka (Khondker et al 2010). This palm grows for ca.…”
Section: Introductionmentioning
confidence: 99%